PROSPECTS FOR ORGANIZING SOCIAL SUPPORT FOR CHILDREN WITH DISABILITIES IN OUR COUNTRY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the pressing issues of social support provided to children with disabilities, its development prospects, and ways to improve it. The conditions created for children with disabilities in the Republic of Uzbekistan, the state policy, legal and regulatory framework, and international experiences are studied. Measures aimed at developing the inclusive education system, improving the functioning of rehabilitation centers, expanding social protection programs, and fostering a positive societal attitude towards children with disabilities are analyzed. In addition, the article highlights the role of special educational institutions, psychological and pedagogical support programs, and mechanisms for integrating children with disabilities into the labor market. Based on the results of the study, practical recommendations are developed to increase the effectiveness of social assistance to children with disabilities and to define strategic directions for the future.